Learning Strategies Used by The British Institute for Upper Intermediate and Advanced Students (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
Practicing is an important factor in learning a second language. People all over the world learn their first language and also second language through practice with other people. Yet, different people may use different ways of learning, which are known as learning strategies. This study is concerned with language learning strategies reported to be used by students of upper intermediate and advanced level at a private language institute in Surabaya. It aims to identify the learning strategies most frequently used by the two groups of respondents and to identify differences and similarities in strategy used by the two groups. This research uses descriptive qualitative method. Using Rebecca Oxford's Strategy Inventory for Language Learning (SILL), the study found that the two groups of respondents used different types of learning strategies. Most frequently used strategies by the upper intermediate students include cognitive, compensation, and meta-cognitive strategies, while the advanced students mostly used social strategies. In addition, the two groups of students showed other differences and some similarities in the strategy use in terms of both type and frequency.